Successful steroid withdrawal guided by surveillance biopsies—A single‐center experience. Issue 3 (6th February 2018) - Wehmeier, Caroline; Hirt‐Minkowski, Patricia; Amico, Patrizia; Georgalis, Argyrios; Hopfer, Helmut; Steiger, Jürg; Dickenmann, Michael; Schaub, Stefan
Abstract: Steroid withdrawal following renal transplantation is challenging and widely debated. This retrospective study aimed at investigating the frequency and determinants of successful steroid withdrawal guided by surveillance biopsies. We analyzed 156 pretransplant DSA‐negative renal transplants receiving basiliximab induction and maintenance immunosuppression with tacrolimus‐mycophenolate‐steroids. The absence of rejection in surveillance biopsies at 3 or 6 months post‐transplant initiated steroid withdrawal, which was monitored by subsequent indication and/or surveillance biopsies. The primary outcome was the frequency of successful (i.e., rejection‐free) steroid withdrawal at 1 year post‐transplant. In the whole study population, successful steroid withdrawal was achieved in 73 of 156 patients (47%). Steroid withdrawal was initiated in 98 of 156 patients (63%) and successful in 73 of 98 patients (74%). Subsequent clinical rejection occurred in only one of 98 patients (1%), whereas 24 of 98 patients (24%) experienced subclinical rejection. Steroid withdrawal was not initiated in 58 of 156 patients (37%) mainly due to current or prior severe (Banff TCMR ≥IA) subclinical rejection. Prediction of successful steroid withdrawal by pretransplant or early post‐transplant parameters was poor. In conclusion, (sub)clinical rejection‐free steroid withdrawal can be expected in about half of pretransplant DSA‐negative patients. As successful steroid withdrawal cannot be well predicted by pre‐ and early post‐transplant parameters, guidance by surveillance biopsies is an attractive strategy.